Substrate Specificity of a Mutant Alanyl-Transfer Ribonucleic Acid Synthetase of Escherichia coli - Buckel, Peter (1971)
The correlation between the in vivo functioning and the in vitro behavior of the thermolabile alanyl-transfer ribonucleic acid (tRNA) synthetase (ARS) of Escherichia coli strain BM113 is presented. As a measure for the ARS activity inside the cell, the amount of acylated tRNA(ala) in vivo was determined. The rapid drop of the per cent tRNA(ala) charged which was observed upon shifting a culture of BM113 to the nonpermissive temperature indicates that in vivo acylation of tRNA(ala) might be the growth-limiting step at high temperature. Since neither growth nor the in vivo charging level of tRNA(ala) was affected by the addition of high l-alanine concentrations to the medium, one may infer that impaired functioning of the mutant enzyme at 40 C seems not to be due to reduced affinity of the enzyme for the amino acid. Separation of bulk tRNA of E. coli and of yeast on benzoylated diethylaminoethyl cellulose and charging of the fractions of the column by wild-type and mutant ARS reveal that only those tRNA species aminoacylated by the wild-type enzyme are also charged by the mutant ARS. Determination of the K(m) values of wild-type and mutant ARS for the three isoaccepting tRNA(ala) species of E. coli shows a ca. 10-fold increase of the apparent K(m) values of the mutant enzyme for all three species. Thus, the mutation proportionally reduces the apparent affinity for tRNA(ala) without causing any detectable recognition errors. Investigation of heat inactivation kinetics of wild-type and mutant ARS without and in the presence of substrates provides further evidence that only the transfer site of the ARS is altered by the mutation. Moreover, whereas both enzymes possess the same pH optimum of the relative maximal velocity, their pH dependence of the K(m) values for tRNA is different. The K(m) of the wild-type enzyme decreases at pH values below 7.0 and that of the mutant enzyme shows the inverse tendency; this again indicates an alteration of the tRNA binding site.